Design An Intelligent Line Following Mobile Robot For Charity Application In Mosque - Nurul Fatiha , Johan (UTeM, 2009)
This project is to design an intelligence of line following mobile robot for charity application in the mosque. Mobile robots have been widely used of application in the industry as well as our daily life. An automatic mobile robot is capable of movement in a given environment. The purpose of this project is to make sure the mobile robot follows along the white line and stop while when it comes face to face with obstacles. It is focus only in the mosque on the Friday prayer. The PIC programming that is attached directly to the controller circuit controls this mobile robot. The robot detects the white line by using two IR sensors consists of transmitter and receiver that are put under the mobile robot and the two other sensors are located at the side to detect any obstacles. The program in the PIC microcontroller board controls this sensor. This robot is driven by two DC motors which are controlled by the program in the PIC 16F877A microcontroller board. The speed is determined by using the pulse width modulation (PWM). This DC motor is used to move the robot in forward direction. It goes forward along the white line and stops if the sensors detect any obstacles nearby it. After a few second that is the timer is controlled by the programming, the robot will go forward again. The mobile robot will move slowly along the white line that is in fiont of the 'saf to get easy to people to put the money in the box given.